Cognitive Functional Therapy for People with Nonspecific Persistent Low Back Pain in a Secondary Care Setting—A Propensity Matched, Case–Control Feasibility Study. Issue 10 (27th March 2020) - Ussing, Kasper; Kjaer, Per; Smith, Anne; Kent, Peter; Jensen, Rikke K; Schiøttz-Christensen, Berit; O'Sullivan, Peter Bruce
Abstract: Background: Effective, inexpensive, and low-risk interventions are needed for patients with nonspecific persistent low back pain (NS-PLBP) who are unresponsive to primary care interventions. Cognitive functional therapy (CFT) is a multidimensional behavioral self-management approach that has demonstrated promising results in primary care and has not been tested in secondary care. Objective: To investigate the effect of CFT and compare it with usual care for patients with NS-PLBP. Design: Case–control study. Setting: A secondary care spine center. Subjects: Thirty-nine patients received a CFT intervention and were matched using propensity scoring to 185 control patients receiving usual care. Methods: The primary outcome was Roland Morris Disability Questionnaire (0–100 scale) score. Group-level differences at six- and 12-month follow-up were estimated using mixed-effects linear regression. Results: At six-month follow-up, a statistically significant and clinically relevant difference in disability favored the CFT group (–20.7, 95% confidence interval [CI] = –27.2 to –14.2, P < 0.001). Significant differences also occurred for LBP and leg pain, fear, anxiety, and catastrophizing in favor of CFT. At 12-month follow-up, the difference in disability was smaller and no longer statistically significant (–8.1, 95% CI = –17.4 to 1.2, P = 0.086). Differences in leg pain intensity and fear remained significantly in favor of CFT. Treatment satisfaction was significantly higher in the CFT group at six- (93% vs 66%) and 12-month (84% vs 52%) follow-up. Conclusions: These findings support that CFT is beneficial for patients with NS-PLBP who are unresponsive to primary care interventions. Subsequent randomized controlled trials could incorporate booster sessions, which may result in larger effects at 12-month follow-up.